2019
DOI: 10.1177/0284185119851236
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the testicular vascularity after inguinal herniotomy in children: a prospective color Doppler study

Abstract: Background Knowing transient vascular perfusion abnormalities of testes after open inguinal herniotomy procedure is essential for the surgeon who is mainly responsible for the patient outcome. Purpose To assess the effect of open inguinal herniotomy procedure on the testicular blood supply in children using duplex ultrasonography (DUS). Material and Methods A prospective observational study included 60 boys (mean age = 9.46 ± 14.46 months; age range = 2 months–6 years) who underwent open inguinal herniotomy op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Some studies have evaluated the effectiveness of IH on testicular perfusion with Doppler US using a resistive index (RI) [15,17]. These studies have shown the testis with IH has a significantly higher RI [18] or that there is no significant difference in the RI values [14,15,[19][20][21]. Studies have also shown that there is no significant alteration of testicular perfusion after IH operation using Doppler US [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated the effectiveness of IH on testicular perfusion with Doppler US using a resistive index (RI) [15,17]. These studies have shown the testis with IH has a significantly higher RI [18] or that there is no significant difference in the RI values [14,15,[19][20][21]. Studies have also shown that there is no significant alteration of testicular perfusion after IH operation using Doppler US [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…All studies compared the preoperative values to the postoperative values, either at short-term follow-up (1 day-1 week) or at long-term follow-up (1 month-6 months). Only Palabiyik et al (2009) and Basha et al (2020) reported a statistically significant difference when comparing the preoperative RI to the early follow-up values (p-value = 0.0008 and <0.0001, respectively) [25,27]. These are the two studies that only report RI after an open surgical approach.…”
Section: Preoperative Resistive Index Compared To Postoperative Resis...mentioning
confidence: 98%
“…A total of 46 articles were excluded because they did not meet the inclusion criteria. Through a full-text assessment of the remaining articles, nine records were identified that were eligible to be included in the systematic review [25][26][27][28][29][30][31][32][33]. The references of these nine papers were screened, and one additional paper was identified as meeting all inclusion criteria [34].…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations